Kajian Yuridis Gugatan Penghapusan Paten Karena Bukan Invensi Baru Dalam Putusan Nomor 47/Pdt.Sus-Paten/2017/Pn.Niaga.Jkt.Pst - Fajar Ariyantono Pangestu; Budi Santoso (Notarius, 2022)
AbstractAdult IPRs are very important in trade competition, including patent rights. It can even be said that a patent is a right that is considered the most valuable compared to other rights. Patents will only be granted to an invention that is new, whether it is an invention of a product, process or method, or tool as mandated by Article 27 of the TRIPS Agreement. However, in reality there are patents that have obtained a Patent certificate even though it is not a new invention, namely Patent ID No P0031670. The research in this article is normative research using qualitative methods, namely an approach to exploring and understanding a central phenomenon. This article has two research results, namely: First, the TRIPS Agreement regulates new inventions in Article 27 while Law No. 13 of 2016 concerning Patents regulates New Patent Invention in Article 5 which is limited by the provisions of Article 6. Second, the judge's consideration in deciding the annulment of Patent No. ID P0031670 because claims 6 to 10 on a patent are not invented and have no novelty value.Keywords: abolition; patents; not novelty inventionsAbstrakDewasa HKI yang sangat penting dalam persaingan dagang, tak terkecuali hak paten. Bahkan dapat dikatakan paten merupakan sebuah hak yang dianggap paling berharga dibandingkan hak yang lainnya. Paten hanya akan diberikan kepada sebuah invensi yang baru, baik invensi produk, proses atau metode, maupun alat sebagaimana amanat Pasal 27 TRIP’s Agreement. Namun, kenyataannya terdapat paten yang mendapatkan sertifikat Paten meskipun bukan invensi baru yaitu Paten No ID P0031670. Penelitian dalam artikel ini adalah penelitian normatif dengan metode kualitatif yaitu suatu pendekatan untuk mengeksplorasi dan memahami sebuah gejala sentral. Artikel ini memiliki dua hasil penelitian, yaitu: Pertama, TRIP’s Agreement mengatur invensi baru dalam Pasal 27 sedangkan UU No. 13 Tahun 2016 Tentang Paten mengatur Invensi Baru Paten dalam Pasal 5 yang dibatasi dengan ketentuan Pasal 6. Kedua, Pertimbangan hakim dalam memutus hapusnya Paten No. ID P0031670 karena klaim nomor 6 sampai 10 pada Paten milik tidak bernilai invensi dan tidak mempunyai nilai kebaruan (novelty).Kata kunci: penghapusan; paten; bukan invensi baru